Tinjauan Pembelajaran Fiqih Mawaris Madrasah Aliyah Tarbiah Islamiyah Kecamatan Hamparan Perak Kabupaten Deli Serdang - Lubis, Sakban; Tumiran, Tumiran; Harahap, Muhammad Yunan; Rahayu, Sinta (Jurnal Keislaman, 2024)
Inheritance is a sensitive issue that often leads to disputes and conflicts within families. In some cultures, sons are often considered to have greater rights to inheritance than daughters. This research aims to evaluate the process of teaching inheritance fiqh (Islamic jurisprudence) in the madrasah, as well as to assess the effectiveness of the methods employed in the teaching process. The research methodology employed is qualitative descriptive method, utilizing data collection techniques such as observation, interviews, and documentary studies. The research findings indicate that the process of teaching inheritance fiqh at Madrasah Aliyah Swasta Tarbiah Islamiyah faces several challenges, including a lack of conceptual understanding, The research findings also highlight insufficient utilization of diverse teaching methods, as well as inadequate learning resources. Based on the analysis, it is recommended to enhance conceptual understanding through a more practical approach, implement innovative teaching methods, and provide comprehensive and up-to-date learning resources. It is hoped that this research will contribute positively to the development of inheritance fiqh teaching in the madrasah.